Security through numbers? Experimentally assessing the impact of numerical arguments in security communication. (May 2018) - Baele, Stephane J; Coan, Travis G; Sterck, Olivier C
Numerical arguments are increasingly present in security communication and are widely assumed to possess a distinct capacity to make an argument convincing, thereby contributing to the dynamics of securitization. Yet, does the inclusion of numbers really enhance the strength of rhetorical attempts to convince an audience that something or someone is a security problem? We examine this question by developing an experimental design that connects cognitive theories of information processing with theories of security and risk communication. Contrary to a widely shared view, our results suggest that numbers do not have a direct, unambiguous, or unconditional impact on the strength of security rhetoric. Quantitative information only enhances direct attempts to securitize issues under very specific circumstances and, even in these cases, has ambiguous effects. Factors such as the legitimacy of the individual who makes the argument may play an important role in determining the impact of numbers in security communication.